What actions should be taken by the corporation so that “concern for the natural environment” would not become just a statement? - Matuszewska-Pierzynka, Agnieszka (W poszukiwaniu zielonego ładu, 2022)
The main goal of the chapter is to answer the research question of what actions the corporation should take so that “concern for the natural environment” would not become just a statement. Seeking an answer to the formulated question, the environmental strategy of Apple Inc., the most admired corporation in the world, has been analyzed, by referring to the assessment of the environmental dimension of the company and its largest American competitors in the computer industry – Dell Technologies Inc. and HP Inc. – in the years from 2017 to 2020.